2019
DOI: 10.3389/fphar.2019.01510
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Excitatory Amino Acid Transporter 2 in Neurological Disorders

Abstract: Excitatory amino acid transporter 2 (EAAT2) is the predominant astrocyte glutamate transporter involved in the reuptake of the majority of the synaptic glutamate in the mammalian central nervous system (CNS). Gene expression can be altered without changing DNA sequences through epigenetic mechanisms. Mechanisms of epigenetic regulation, include DNA methylation, post-translational modifications of histones, chromatin remodeling, and small non-coding RNAs. This review is focused on neurological disorders, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 115 publications
(107 reference statements)
0
9
0
Order By: Relevance
“…Based on a study of the mammalian central nervous system, it has been shown that Excitatory Amino Acid Transporter 2 (EAAT2) is the dominant astrocyte glutamate transporter related to the reuptake of synaptic glutamate in the mammalian central nervous system (CNS) (Alam and Datta, 2019). Gene expression can be regulated without altering DNA sequences through epigenetic mechanisms (D'Addario and Maccarrone, 2016).…”
Section: Neurodevelopmental Neurological and Behavioral Regulation With Crispr/cas Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a study of the mammalian central nervous system, it has been shown that Excitatory Amino Acid Transporter 2 (EAAT2) is the dominant astrocyte glutamate transporter related to the reuptake of synaptic glutamate in the mammalian central nervous system (CNS) (Alam and Datta, 2019). Gene expression can be regulated without altering DNA sequences through epigenetic mechanisms (D'Addario and Maccarrone, 2016).…”
Section: Neurodevelopmental Neurological and Behavioral Regulation With Crispr/cas Systemmentioning
confidence: 99%
“…Gene expression can be regulated without altering DNA sequences through epigenetic mechanisms (D'Addario and Maccarrone, 2016). This highlights the evidence for the role of epigenetics in the regulation of EAAT2 in different neurological disorders and discusses the current pharmacological approaches used to induce EAAT2 expression with CRISPR/Cas9 technology, and the potential use of new therapeutic approaches (Alam and Datta, 2019).…”
Section: Neurodevelopmental Neurological and Behavioral Regulation With Crispr/cas Systemmentioning
confidence: 99%
“…Treatments to inhibit both DNA methyltransferase (an epigenetic ‘writer’ that causes epigenetic transcriptional repression) and HDAC (which likewise leads to transcriptional repression) were successfully able to increase astrocytic EAAT2 expression in these glioma cell lines [ 135 ]. These findings raise the possibility of targeting epigenetic mechanisms as a way of controlling astrocytic EAAT expression in the context of disease [ 137 ].…”
Section: Astrocytic Eaat Regulationmentioning
confidence: 99%
“…Growing evidence shows that dysregulation of these transporters plays a significant role in excitotoxicity and associated neuropathogenesis. The expression and function of these astrocytic transporters may be dysregulated at the genetic, epigenetic, transcriptional or translational levels, leading to high levels of extracellular glutamate and excitotoxicity 39,[55][56][57][58][59] . On the other hand, the neuronal EAAT3 is ubiquitously expressed in the brain, it is important in maintaining low local concentrations of glutamate, where its predominant post-synaptic localization can buffer nearby glutamate receptors and modulate excitatory neurotransmission and synaptic plasticity 60 .…”
Section: Introductionmentioning
confidence: 99%
“…EAAT2 is primarily expressed in astrocytes and select neurons and oligodendrocytes of the brain and spinal cord , and accounts for approximately 95% of the total l -glutamate transport activity and 1% of total brain protein in the Central Nervous System (CNS). ,, Growing evidence shows that dysregulation of these transporters plays a significant role in excitotoxicity and associated neuropathogenesis. The expression and function of these astrocytic transporters may be dysregulated at the genetic, epigenetic, transcriptional, or translational levels, leading to high levels of extracellular glutamate and excitotoxicity. , On the other hand, the neuronal EAAT3 is ubiquitously expressed in the brain, it is important in maintaining low local concentrations of glutamate, where its predominant postsynaptic localization can buffer nearby glutamate receptors and modulate excitatory neurotransmission and synaptic plasticity . Several diseases implicate in dysfunction of EAAT3, such as epilepsy, obsessive-compulsion disorder, and schizophrenia .…”
Section: Introductionmentioning
confidence: 99%